2021
DOI: 10.1111/jpc.15675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and laboratory profile of survivors and non‐survivors of SARS‐CoV‐2‐related multisystem inflammatory syndrome of childhood in India: An observational study

Abstract: Aim The SARS‐CoV‐2 pandemic is characterised by multiple reports of paediatric multisystem inflammatory disease or multisystem inflammatory syndrome in children (MIS‐C) with Kawasaki disease‐like features often complicated by myocarditis, shock and macrophage activation syndrome. Certain clinical and laboratory markers may be used to identify high risk cases. Methods All sequentially admitted patients hospitalised between April 2020 and October 2020, who met the WHO case definition for MIS‐C were included. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
(36 reference statements)
4
11
0
Order By: Relevance
“…The mortality observed in the present study subjects is strikingly higher than other large series from developed nations (10.87% vs. 1%-2%). High mortality (27.5%) has also been reported from a single-center study from India, which has not participated in the present study [12].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The mortality observed in the present study subjects is strikingly higher than other large series from developed nations (10.87% vs. 1%-2%). High mortality (27.5%) has also been reported from a single-center study from India, which has not participated in the present study [12].…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, a retrospective study in a French cohort with 181 children also showed a favorable outcome in terms of early defervescence, the requirement of inotropic support, and duration of intensive care stay in the group receiving both IVIG and methylprednisolone as compared to IVIG alone [8]. However, there were differences in the predefined primary outcomes of these studies [10][11][12]; cardiac dysfunction or shock on or after day 2 in the study by Son et al [9]; the persistence of fever 2 d after the introduction of initial therapy or recrudescence of fever within 7 d in the French cohort [8], compared to the composite outcome (requirement of vasoactive/inotropic support for ≥ 2 d or need of mechanical ventilation ≥ 2 d after initiation of immunomodulatory treatment or death during hospitalization), in the Best Available Treatment Study (BATS) by McArdle et al [10]. In the present study, death was also included as a primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate (12.9%) observed in the present series is in stark contrast to that reported from multi-hospital data from US [ 8 , 21 ]. The reported mortality in Indian series ranges from 0 to 27.5% [ 14 , 15 , 24 ]. All children who succumbed to illness in our series had underlying comorbidities, which might have contributed to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The only series reporting higher mortality (27.5%) than ours, by Maheshwari et al didn’t mention about the underlying comorbidities. The other speculated factors contributing toincreased mortality in resource-poor settings include delayed referral to tertiary care centers and delay in instituting timely immunomodulation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher rate of death (11.2%) noted in our study is similar to that reported in previous Indian study (12.9%) ( 13 ). Other Indian studies have reported mortality rate varying from 0 to 27.5% ( 17 , 18 , 31 ). However, these figures are much higher than those reported in the previous systematic review, and multi-center data from USA ( 12 , 15 ).…”
Section: Discussionmentioning
confidence: 96%